1995
DOI: 10.1137/0732033
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Finite Element Methods for Parabolic Problems II: Optimal Error Estimates in $L_\infty L_2 $ and $L_\infty L_\infty $

Abstract: Optimal error estimates are derived for a complete discretization of linear parabolic problems using space-time finite elements. The discretization is done first in time using the discontinuous Galerkin method and then in space using the standard Galerkin method. The underlying partitions in time and space need not be quasi-uniform and the partition in space may be changed from time step to time step. The error bounds show, in particular, that the error may be controlled globally in time on a given tolerance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
154
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(155 citation statements)
references
References 9 publications
1
154
0
Order By: Relevance
“…The relation (1.4) is an optimal-order error estimate provided we do not change the spaces S n h too often-compare with the results of Dupont [D]; but even in this case (1. [EJ2], show that optimal order-regularity estimates (up to a logarithmic factor) are valid for the corresponding discontinuous Galerkin method for linear parabolic problems, provided in each time slab either S n h ⊂ S n−1 h or k n ≥ ch 2 n . The approach in [EJ1], [EJ2] is based on establishing "strong" stability estimates for an appropriate discrete dual problem.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relation (1.4) is an optimal-order error estimate provided we do not change the spaces S n h too often-compare with the results of Dupont [D]; but even in this case (1. [EJ2], show that optimal order-regularity estimates (up to a logarithmic factor) are valid for the corresponding discontinuous Galerkin method for linear parabolic problems, provided in each time slab either S n h ⊂ S n−1 h or k n ≥ ch 2 n . The approach in [EJ1], [EJ2] is based on establishing "strong" stability estimates for an appropriate discrete dual problem.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…[EJ2], show that optimal order-regularity estimates (up to a logarithmic factor) are valid for the corresponding discontinuous Galerkin method for linear parabolic problems, provided in each time slab either S n h ⊂ S n−1 h or k n ≥ ch 2 n . The approach in [EJ1], [EJ2] is based on establishing "strong" stability estimates for an appropriate discrete dual problem. These estimates depend in an essential manner on the parabolic character of the problem considered in [EJ1], [EJ2].…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us mention the work of Dupont (1982), Eriksson & Johnson (1991, 1995 and Yang (2000). In the pioneering work of Dupont (1982), for a one-dimensional parabolic model problem, it is shown that changing the mesh in a particular way in each time step leads to convergence of the numerical solution to a wrong answer.…”
Section: Introductionmentioning
confidence: 99%
“…In the pioneering work of Dupont (1982), for a one-dimensional parabolic model problem, it is shown that changing the mesh in a particular way in each time step leads to convergence of the numerical solution to a wrong answer. In Eriksson & Johnson (1991, 1995 an a priori error analysis based on duality arguments is given for finite element approximations of a class of parabolic problems. Optimal-order error estimates are established under restrictions on the mesh changes, which have to satisfy either that the finite element spaces are embedded, T n ⊂ T n−1 , or that the restriction h 2 n CΔt n on the discretization step sizes is satisfied, where h n and Δt n denote the spatial and temporal step size, respectively, and C is a constant.…”
Section: Introductionmentioning
confidence: 99%